ENTREPRENEURIAL SUCCESSION PROBLEMS IN NIGERIA’S FAMILY BUSINESSES: A THREAT TO SUSTAINABILITY - O.J.K., Ogundele (European Scientific Journal, ESJ, 2012)
The need to focus on entrepreneurial succession problems in Nigeria is due to the fact that many promising family businesses have collapsed over the years soon after the demise/exit of their founders. Using secondary data, the paper seeks to explore the issues involved in succession problems, the sources of the problems and how these have threatened the perpetuity principle in companies with respect to family businesses in Nigeria. The paper concludes that the succession laws of Nigeria (which includes the native laws and customs) and the multi-cultural nature of Nigeria creates a myriad of succession problems for familyowned businesses in Nigeria. Based on its findings, the paper recommends to indigenous Entrepreneurs in Nigeria, the crafting of a comprehensive, well thought-out, market-focused and people-centered entrepreneurial succession planning started early enough in the life of the business.